Domain separation and characterization of PriC, a replication restart primosome factor in Escherichia coli. (2nd July 2013) - Aramaki, Takahiko; Abe, Yoshito; Ohkuri, Takatoshi; Mishima, Tomonori; Yamashita, Shoji; Katayama, Tsutomu; Ueda, Tadashi
<x xml:space="preserve">Abstract</x> In Escherichia coli the oriC‐independent primosome plays an essential role in replication restart after dissociation of the replication DNA–protein complex by DNA damage. Primosome is thought to form via two pathways: one PriA dependent and the other PriA independent. PriC is a key protein in the replication restart of the PriA‐independent pathway. In this study, we determined that PriC was divided into two domains. Then, we obtained information that: (i) the C‐terminal domain preferentially binds to single‐stranded DNA (ssDNA); (ii) the binding of PriC to ssDNA depends on salt concentration; and (iii) the binding site size of PriC is approximately 7–9 nucleotides. The protease digestion of PriC suggested that a possible DNA‐binding site is the N‐terminus of the C‐terminal domain where basic amino acid residues are concentrated. Interestingly, α‐helical induction of the C‐terminal domain of PriC occurred after the addition of DNAs. Also, we examined the role of heptad repeat of leucine or valine residues in the C‐terminal domain and PriC oligomerization. This study describes the structure and function analysis of PriC which forms the primosome complex in replication restart.